ANALISIS FAKTOR WILLINGNESS TO PAY PENGUNJUNG PADA OBJEK WISATA TEBA PANOTANG KABUPATEN SUMBAWA - Pranata, Yudi; Karmeli, Elly (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to analyze the factors that affecting on visitors' willingness to pay at the Teba Panotang tourist object, Sumbawa District. These factors are education (X1), income (X2), frequency of visits (X3), duration of visits (X4), and cost of visits (X5). The type of this study was assosiative study. The type of data used in this study was quantitative data obtained directly from respondents using a questionnaire. The respondents in this study were visitors to the Teba Panotang tourist object, totaling 30 people who were determined using non-probability sampling techniques using the accidental sampling (convenience sampling) method. Data analysis was carried out using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and coefficient of determination test (R2). The results of this study showed that partially education had not effect on visitors' willingness to pay, while income, frequency of visits, and duration of visits had a positive and significant effect on visitors' willingness to pay, and visit costs had a negative and significant effect on visitors' willingness to pay. Simultaneous test results showed that education, income, frequency of visits, duration of visits, and cost of visits had a significant effect on visitors' willingness to pay at the Teba Panotang tourist object, Sumbawa District. The ability of the independent variables contained in this study model to explain the visitors' willingness to pay at the Teba Panotang tourist object was 73.1%, while the remaining of 26.9% was effected by other variables outside this research model.